Analisis Diskriminasi Kerja Karyawan Disabilitas Dengan Menggunakan Teknik Bibliometrik - Tani, Lukas Greddyansyah; Zagladi, Arief Noviarakhman (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Aim: This article aims to provide a comprehensive bibliometric analysis of the literature on workplace discrimination against employees with disabilities over the last ten years and to identify recent research trends. Methods: This study employs a descriptive bibliometric analysis using data from 2012-2022. Data were collected from the Google Scholar database with the keyword employment discrimination of employees with disabilities, processed using Publish or Perish software, and filtered to obtain 183 relevant journals. After data processing, the researchers used VOSviewer to categorize and visualize co-authorship, co-occurrence, and citations. Findings: The results indicate shifts in research trends on workplace discrimination over the past decade, reflected in co-authorship patterns, co-occurrence, and citation networks within the literature. Originality: This article provides a foundation for future studies on workplace discrimination against disabled employees. Practical Implications: Companies offering employment opportunities for disabled employees must provide inclusive work facilities to foster a diverse work culture that benefits both disabled and non-disabled employees. Additionally, governments should establish regulations to protect the rights of disabled employees. Research Limitations: This study is limited to ten years, using only one database (Google Scholar), excluding books as references, including only English-language articles, and utilizing a single keyword. Future research is encouraged to expand the scope of years, databases, and languages used in analysis.